2022
DOI: 10.1227/neu.0000000000002088
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Baseline Frailty Status in Traumatic Spinal Cord Injury

Abstract: BACKGROUND: Literature evaluating frailty in traumatic spinal cord injury (tSCI) is limited. OBJECTIVE: To evaluate the prognostic significance of baseline frailty status in tSCI. METHODS: Patients with tSCI were identified in the National Inpatient Sample from 2015 to 2018 and stratified according to frailty status, which was quantified using the 11-point modified frailty index (mFI). RESULTS: Among 8825 operatively managed patients with tSCI identified (mean age 57.9 years, 27.6% female), 3125 (35.4%) were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We acknowledge that this proposition contrasts with existing trends in the literature citing increased surgical risk associated with advanced age ( Tsujimoto et al, 2022 ; Arul et al, 2019 ). Despite this, there is a growing body of literature endorsing the use of frailty scores as a superior measure of risk stratification and true physiologic status compared to chronological age ( Mehkri et al, 2023 ; Kessler et al, 2018 ; Sun et al, 2020 ; Dicpinigaitis et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that this proposition contrasts with existing trends in the literature citing increased surgical risk associated with advanced age ( Tsujimoto et al, 2022 ; Arul et al, 2019 ). Despite this, there is a growing body of literature endorsing the use of frailty scores as a superior measure of risk stratification and true physiologic status compared to chronological age ( Mehkri et al, 2023 ; Kessler et al, 2018 ; Sun et al, 2020 ; Dicpinigaitis et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association of clinical frailty with poor outcomes among patients with spinal pathology has been frequently studied 29 33 . However, most of these studies pertain to degenerative spine disease, with more limited evidence in the setting of acute SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, frailty has been increasingly recognized as a common feature affecting surgical outcomes, such as increased risk of postoperative complications, mortality, and prolonged hospital stay. The mFI-11 index is used to evaluate frailty and predict postoperative mortality and morbidity ( 18 , 38 ); for example, Dicpinigaitis and colleagues reported that higher mFI-11 score is associated with development of severe complications, but not with in-hospital mortality or extended length of stay ( 39 ). In addition, Heimann et al.…”
Section: Discussionmentioning
confidence: 99%